Feed conversion in Oreochromis niloticus fry using multifunctional feed at 24% and 14% protein - Hernández Rivera, C. I.; Urbina-Flete, Santiago Noel; Altamirano-Pérez, Melba Regina (Rev. iberoam. bioecon. cambio clim., 2024)
Background: Tilapia (Oreochromis niloticus) is of commercial and nutritional importance for Nicaraguan families. Objective: To evaluate the growth of tilapia in liner ponds, using two types of multifunctional feed containing 24% and 14% protein. Methodology: Two ponds (G1 and G2) were selected, each with a capacity of 90 tons of water, in a semi-intensive production system. Both ponds were stocked with a density of 13 fish/m², with initial average weights of 22.9 g in G1 with a multifunctional feed source of 24% protein and 20.2 g in G2 with a multifunctional feed of 14% protein. Weekly biometric monitoring was performed for 9 weeks, as well as a record of physicochemical parameters twice a day, except for turbidity, which was measured at 12:00 p.m. Results: The results indicated that the physicochemical parameters remained within optimal ranges throughout the culture, without significant variations. Additionally, the analysis of the microalgae density in the pond revealed that the multifunctional feed with 24% protein not only favored the increase in biomass, but also improved the natural productivity of the ecosystem. The growth recorded in the pond with the 24% protein feed reached 135g, compared to 98g in the pond with 14% protein feed. Conclusion: The treatments under study presented a Feed Conversion Factor of 0.7 at the end of the culture, these results reinforce the importance of protein content in the growth of tilapia.